2012
DOI: 10.1007/s10571-012-9810-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sensory Responses in Osteocalcin Null Mutant Mice Imply Neuropeptide Function

Abstract: Osteocalcin, the most abundant member of the family of extracellular mineral binding gamma-carboxyglutamic acid proteins is synthesized primarily by osteoblasts. Its affinity for calcium ions is believed to limit bone mineralization. Several of the numerous hormones that regulate synthesis of osteocalcin, including glucocorticoids and parathyroid hormone, are also affected by stressful stimuli that require energy for an appropriate response. Based on our observations of OC responding to stressful sensory stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Mice were evaluated for behavior in the light/dark box, open field, and on a 4°C cold plate. These data were reported previously (Patterson-Buckendahl, Sowinska et al 2012). Following these tests, we evaluated taste preferences for saccharin, capsaicin, and menthol, for which there were no significant genotypic differences (data not shown).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Mice were evaluated for behavior in the light/dark box, open field, and on a 4°C cold plate. These data were reported previously (Patterson-Buckendahl, Sowinska et al 2012). Following these tests, we evaluated taste preferences for saccharin, capsaicin, and menthol, for which there were no significant genotypic differences (data not shown).…”
Section: Methodssupporting
confidence: 91%
“…Furthermore, KO could be less sensitive to those prior conditions such that their drinking was less affected, or they might be less sensitive to intoxication resulting from the ETOH consumption. We have previously documented decreased sensitivity by KO in response to varous physical stimuli, including injections (Patterson-Buckendahl, Sowinska et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Routine handling of the osteocalcin null mice suggested that cognition in the mutant mice was impaired relative to control littermates, and more formal behavioral testing revealed an increase in behaviors associated with anxiety and depression (64). A previous study had indicated that osteocalcin is produced in the brain and might function as a neuropeptide (65). However, work by Oury and colleagues (64) demonstrated that circulating osteocalcin crosses the blood-brain barrier and acts in the brainstem, midbrain, and hippocampus to influence the synthesis of several neurotransmitters that favor learning and memory formation.…”
Section: A Role For Osteocalcin In Fertility and Cognitionmentioning
confidence: 99%
“…Guilu Erxian Glue (GEG), which comprises four major components, Testudinis Plastrum , Cornu Cervi , Lycii Fructus , and Ginseng Radix , is a Chinese herbal remedy that has long-lasting favorable effects on aging, perimenopausal syndrome, and degenerative joint diseases in Asia [ 23 – 25 ]. Recent studies have also mentioned that GEG can stimulate the secretion of IGF-1 in osteoblasts and attenuate the bone resorption activity of osteoclasts in vitro [ 26 ], inhibit the formation of osteoclasts and bone pits in rats [ 27 ], and decrease articular pain and increase muscle strength in elderly men with knee OA [ 28 ]. However, knowledge about the mechanisms responsible for the beneficial effects of GEG in OA is limited.…”
Section: Introductionmentioning
confidence: 99%